Islamic Republic of Iran : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Islamic Republic of Iran. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights a rebound in economic growth in the Islamic Republic of Iran over the course of 2016-17 based on higher oil production. Real GDP grew 7.4 percent in the first half of 2016-17, rebounding from the 2015-16 recession. However, growth in the non-oil sector averaged 0.9 percent, despite having picked up in the second quarter, reflecting continued difficulties in access to financing and domestic financial sector and structural weaknesses. Growth is projected to stabilize at 4.5 percent over the medium term as the recovery broadens. The current account is forecast to remain in surplus as higher exports offset the pickup in imports related to investment.